Effects of pressure and fluid properties on P-wave velocity and attenuation of tight sandstones - Ba, Jing; Pan, Xuming; Carcione, José M.; Ma, Rupeng (Frontiers in Earth Science, 2023)
Tight reservoirs are distributed in several basins in China, with great exploration prospects and high production potential. These reservoirs have low porosity and permeability and a significant spatial heterogeneity, and this complexity requires new developments on the experimental and theoretical researches of wave propagation. To this purpose, we have conducted ultrasonic experiments on seven tight sandstones collected from the shale-oil strata as a function of the confining pressure. We obtained the P-wave velocity and attenuation by using the spectral-ratio method. The results show that attenuation decreases with pressure, and increases with porosity and permeability and that oil saturation causes more losses compared to water and gas saturations. Moreover, we observe a relaxation peak at 40% water saturation in the gas-water case. Then, we develop a tight-rock model combining three theories [Voigt-Reuss-Hill (VRH), Differential Effective Medium (DEM) and double double-porosity (DDP)], where inclusions are assumed to represent cracks or grain contacts, with different porosity and compressibility as the host. The model reasonably predicts P-wave velocity dispersion and attenuation, which increase with water saturation, and the related relaxation frequency moves to low frequencies.